2020
DOI: 10.3390/rs12203385
|View full text |Cite
|
Sign up to set email alerts
|

Landslide Characterization Applying Sentinel-1 Images and InSAR Technique: The Muyubao Landslide in the Three Gorges Reservoir Area, China

Abstract: Landslides are a common natural hazard that causes casualties and unprecedented economic losses every year, especially in vulnerable developing countries. Considering the high cost of in-situ monitoring equipment and the sparse coverage of monitoring points, the Sentinel-1 images and Interferometric Synthetic Aperture Radar (InSAR) technique were used to conduct landslide monitoring and analysis. The Muyubao landslide in the Three Gorges Reservoir area in China was taken as a case study. A total of 37 images f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(46 citation statements)
references
References 40 publications
(49 reference statements)
3
43
0
Order By: Relevance
“…Second, groundwater seepage caused by the drawdown of the reservoir water level decreased landslide stability. When the reservoir level drops rapidly, the dissipation of pore water pressure in the landslide body is slower than the decrease of external hydrostatic pressure [18,43,44]. The transient seepage induced by this lagging effect creates seepage force along the sliding direction [45], which increased the slip force and further reduced slope stability.…”
Section: Characterizing the Development Pattern Of The Landslidementioning
confidence: 99%
See 1 more Smart Citation
“…Second, groundwater seepage caused by the drawdown of the reservoir water level decreased landslide stability. When the reservoir level drops rapidly, the dissipation of pore water pressure in the landslide body is slower than the decrease of external hydrostatic pressure [18,43,44]. The transient seepage induced by this lagging effect creates seepage force along the sliding direction [45], which increased the slip force and further reduced slope stability.…”
Section: Characterizing the Development Pattern Of The Landslidementioning
confidence: 99%
“…Although colluvial landslides show evidence of deformation at low velocities, in situ monitoring is helpful in detecting their temporal evolution [13,14]. Some studies have shown that remotely sensed techniques also play an essential role in the observation of landslide deformation [15][16][17][18]. Capturing the relationship between the hydrological and kinematic responses of these slow-moving colluvial landslides is key to analyzing their development [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…ML has been used in landslide research for landslide detection [7], characterization [8], susceptibility assessment [9]- [11], prediction [12], and early warning systems [13]. The most common ML algorithms used are support vector machines [7], [9]- [11], followed by logistic regression [7], [10], [11], random forests [7], [9], artificial neural networks [9], [11], and Bayesian networks [9], [10].…”
Section: Introductionmentioning
confidence: 99%
“…Ground deformation resulting from variations in the volume of surface water resources, such as impounded reservoirs, can also trigger landslides and sudden mass movements; if these feed into lakes. Associated large surges of water can lead to dam instability, threatening lives and properties along the shores [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%